Disassembly of a dune‐dwelling lizard community due to landscape fragmentation. Issue 8 (20th August 2013) - Leavitt, Daniel J.; Fitzgerald, Lee A.
Abstract : Landscape fragmentation alters patterns of landscape structure that affect quality and configuration of habitats, and disrupts population dynamics and persistence of species. Community disassembly, a process of community change due to nonrandom species losses and declines, is occurring worldwide as a result of landscape fragmentation, habitat loss, and habitat degradation. We carried out a comparative study at 27 trapping sites designed to characterize how fragmentation affects community structure in a dune‐dwelling lizard community. Lizard communities in non‐fragmented sites demonstrated nested community structure. Conversely, lizard communities at sites fragmented by roads and well pads from oil and gas development had consistently lower abundance of two species, and demonstrated random community structure. Species loss and lower abundance of species at fragmented sites suggested a pattern of community disassembly. The dunes sagebrush lizard ( Sceloporus arenicolus ), an ecological specialist, and the lesser earless lizard ( Holbrookia maculata ) were present on most non‐fragmented sites. However, neither species was present on more than half of the fragmented sites, and their abundances were much lower than on non‐fragmented sites. We attributed reduced species diversity on fragmented sites to quantitative differences in landscape configuration compared to non‐fragmented sites. Specifically, both size and shape of sand dune blowouts differed between non‐fragmented and fragmented sites. Fragmented sites possess more large patches of open sand and barren ground and fewer, smaller, and more dispersed shinnery dune blowouts. Patterns of occurrence and relative abundance suggest S. arenicolus and H. maculata were sensitive to these patch‐scale attributes. In this ecosystem, landscape‐scale fragmentation appears to influence landscape configuration and community disassembly at the patch‐scale. Our findings allow us to disentangle drivers of species loss and enhance our understanding of the processes of community disassembly in fragmented landscapes.